PENDUGAAN UMUR SIMPAN KACANG TANAH BERLEMAK RENDAH DENGAN MODEL ARRHENIUS DAN SORSPI ISOTHERMIS [Shelf Life Prediction of Partially Defatted Peanuts Using Arrhenius and Sorption Isotherm Models] - Adil Basuki Ahza; Puguh Setiawan; Muhammad Arpah (Jurnal Teknologi dan Industri Pangan, 1999)
Partially defatted peanuts snack food was produced by reducing part of the oil content using hydraulic pressing, followed by reconstituting to again the normal shape and drying in a microwave oven. This research was conducted to select the optimum pressing process and to predict the shelf life of partially defatted peanuts by Arrhenius and sorption isotherm models. Average percentage of broken kernel was found to be 1.85±0.58%. The lowest fat contentwas 34.82±1.75% produced by 3000 psi pressure for 30 minutes. Prediction of the shelf life of partially defatted peanut by Arrhenius models resulted in a quality-loss constant (i.e rate constant K) of 0.0637 mmol/kg per day (peroxide value-parameter). Packaging in a 29.92 mm thick, 6.5 cm x 6 cm size LDPE for 10 gram solid weight of product at 30°C and 75% RH resulted in the shelf life of 489 days.